Determination of Some Physical and Mechanical Properties of Laminated Scots Pine Using Polylactic Acid in the Middle Layers - Oğuzhan Uzun; Mehmet Sarıkahya; Veysel Tokdemir; Mehmet Nuri Yildirim (BioResources)
Mechanical and physical properties were determined for laminated Scots pine (Pinus sylvestris L.) using polylactic acid (PLA). Structural parts were produced via 3D printing with additive manufacturing (FDM: fused deposition modeling) method in the middle layers. For this purpose, PLA parts with 30%, 60%, and 90% filling rates were glued to the middle of the 5-layer laminated material with polyurethane (PU) glue, and physical and mechanical tests were conducted according to the relevant standards. It was found that increasing the filler content resulted in higher density, reduced water absorption and thickness swelling, increased bending strength and modulus of elasticity, while screw holding resistance increased by approximately 75%. Compressive strength parallel to the fibers showed comparable results to control samples. These findings suggest that PLA filler particles can serve as an alternative middle layer material in wood lamination, offering potential for minor but meaningful improvements in specific applications.